2022
DOI: 10.1139/bcb-2021-0275
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate inhibits proliferation, migration, and invasion of thyroid cancer cells by regulating the PI3K/AKT/FKHR pathway

Abstract: This study characterized the effects of artesunate on thyroid cancer and partially identified its related molecular mechanism. We determined the effect of artesunate on the proliferation of thyroid cancer cells using the MTT assay, cell colony formation experiments, and western blotting, and used flow cytometry to detect the apoptosis of cancer cells. Using a wound-healing assay, Transwell chamber experiments, and western blotting, we determined the effect of artesunate on cancer cell migration. By co-cultivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…ART, a Chinese herbal medicine, regulates many cellular processes and has been proved to be a potent anticancer drug in many tumors has been proved (Jia et al 2023 ; Xu et al 2022 ; Li et al 2021 ). Studies found ART regulated Eph/ephrin signaling pathway in different cancers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ART, a Chinese herbal medicine, regulates many cellular processes and has been proved to be a potent anticancer drug in many tumors has been proved (Jia et al 2023 ; Xu et al 2022 ; Li et al 2021 ). Studies found ART regulated Eph/ephrin signaling pathway in different cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies have focused on the anticancer effects of Artesunate (ART) which is a derivative of artemisinin. ART can play a cancer-suppressing role in many tumors by promoting apoptosis, autophagy, inhibiting cell proliferation and angiogenesis, etc., such as lung cancer, thyroid cancer and colorectal cancer (Wang et al 2020a ; Xu et al 2022 ; Huang et al 2022 ). ART shows promise as an anticancer drug by inhibiting many classical pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [132] found strong anti-proliferative effects of ARS in medullary thyroid carcinoma cells and in chemo resistant anaplastic thyroid cancer [133]. It inhibited proliferation, migration, and invasion by targeting the P13K/AKT pathway [134].…”
Section: O Thyroid Carcinomamentioning
confidence: 99%
“…It has been repurposed as an anticancer drug because it induces multiple forms of PCD, including apoptosis, autophagy, and ferroptosis . ART induces apoptosis and inhibits the proliferation and migration of thyroid cancer cells by inhibiting the PI3K/AKT/FKHR signaling pathway . However, whether ART induces ferroptosis in PTC cells and improves PTC therapy remains elusive.…”
Section: Introductionmentioning
confidence: 99%